Analisis Pengaruh Service Quality Dan Brand Image Terhadap Customer Loyalty Dengan Customer Satisfaction Sebagai Variabel Intervening - Wowiling, Timothy (Universitas Sam Ratulangi, 2019)
The results shows that service quality does not significantly influence the customer satisfaction of Mercure Manado Tateli Resort and Convention, brand image has a significant effect on customer satisfaction of Mercure Manado Tateli Resort and Convention, service quality does not significantly influence customer loyalty of Mercure Manado Tateli Resort and Convention, brand image does not significantly influence the customer loyalty of Mercure Manado Tateli Resort and Convention and customer satisfaction has a significant effect on customer loyalty of Mercure Manado Tateli Resort and ConventionKeywords: Service Quality, Brand Image, Customers Satisfaction and Customer Loyalty